Development of a stingray robot - Mohd. Hafiz, Baharuddin (2012)
This project involves the design and construct of biological inspired underwater robot that mimicking the stingray maneuverability. The robot will be design based on the shape of stingray, and has the abilities to swim like a stingray. There were three major parts in constructing the robot; mechanical design, electronic circuitry and software design. In the mechanical part, body frame and fins is design carefully in order to make the movement of the robot smooth underwater. 4 servo motors and DC motors are used to move the robot forward and downward (submerge). Flapping motion is performed by the servos rotation controlled by the PIC18F4550 microcontroller.